Action-Oriented Teaching: A German Framework for Integrating Theory and Socio-Professional Practice - Chi, Diep Phuong; Hartmann, Martin D. (Journal of Teaching and Learning, 2026)
The primary objective of this study is to develop a comprehensive theoretical framework for the action-oriented teaching perspective, grounded in the German approach, widely adopted in German-speaking countries. The article proposes a process that teachers can use to design and implement action-oriented teaching to enhance students’ application of academic content in realistic professional situations and social contexts. This study follows a qualitative approach, employing systematic literature review, grounded theory, and thematic analysis methods. The findings reveal that action-oriented teaching has a strong psychological foundation. When analyzed in relation to cognitive and skills taxonomies, and empirical data from Germany and Vietnam, this concept demonstrates its capacity to foster learners’ complex competencies—particularly their ability to apply theoretical knowledge in professional and social contexts. Action-oriented teaching can be implemented through various methods, such as project-based learning, experimentation, design tasks, fabrication tasks, debates, role-plays, and case studies. A key aspect of this concept is that learners actively engage in comprehensive actions to create material (tangible) or verbal learning products, which result from situation-oriented learning tasks. This framework helps address key educational challenges, including student engagement, competency development, and the integration of theory and practice. Its interdisciplinary and cross-cultural relevance makes it valuable for educators, policymakers, and researchers across vocational, general, and higher education contexts.